THE EVALUATION OF SAFETY AND ADVERSE EFFECTS OF TRANSCRANIAL MAGNETIC STIMULATION IN PATIENTS WITH MUSCULAR DYSTONIA - T. N. Charnukha; S. A. Likhachev; V. U. Hleb; G. V. Zabrodzets (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
It was aimed to evaluate safety and adverse effects of rhythmic transcranial magnetic stimulation (rTMS) in patients with muscular dystonia (MD). There were treated 163 patients. It was proved that the use of low-frequency rTMS is well tolerated. The obtained results allows to recommend rTMS in the complex system of treatment and rehabilitation of patients with MD.